The role of e-business and web design in expanding the scope of product marketing in grutty shoe stores - Sutopo Sutopo; Sudianto Sudianto; Abdul Hamid; Anang Martoyo (SINTESA, 2023)
E-business involves communicating and conducting business electronically via the Internet. Ebusiness can be significantly improved by strengthening the value chain relationship between businesses (B2B) and consumers (B2C). Today's e-Business environment allows manufacturers to automate and integrate functions like never before - from customer relationship management, to supply chain. Web design has a strong influence on the scope of product marketing, especially at the marketing point. Web design is an important tool in marketing strategy. When web design and marketing work together to combine effective content with a well-designed site, marketing efforts receive the boost needed to get ahead of the competition and convert more visitors into customers. A strategically designed and attractive website will attract more visitors and help convert those visitors into leads. This will definitely result in increased income which will certainly benefit the Company. Marketing arouses user interest and encourages the purchase of certain items, whereas design attracts users and helps communicate a brand's message to its audience. Without these two services, a business is incomplete. The purpose of this research is to find out the role of e-business, web design, and product marketing scope in grungy shoe stores. The method uses a qualitative research approach and literature study (Library Research) which is useful for obtaining a series of descriptions of the factors that influence the results of the variables studied. This research step uses data collection methods from online journal literature sourced from Google Scholar. The results of e-business research influence consumers in expanding the scope of product marketing, Web design influences (has a negative impact) on the product marketing scope variable, which means that the lower the web design, the lower the product marketing scope in expanding product marketing. In conclusion, the role of ebusiness in expanding product marketing at grungy shoe stores has functioned well, including as a market breakthrough: because of its function as a global medium, markets that were previously unknown or impenetrable can be penetrated when utilizing internet technology. As market development: new geographical markets can be entered because of their function as a global medium, bringing together companies and buyers, complete information is also obtained through many applications and online methods, so new segments will be formed. Apart from that, the role of web design in expanding product marketing at grungy shoe stores is functioning well. Web design has an influence (has a negative impact) on product marketing, which means that the lower the quality of the web design, the lower the product marketing will be in expanding the marketing scope of a product. Web design has a big influence on buyers when deciding on purchasing decisions, web designmoderated by e-business expands product marketing. Although good web design does not guarantee good product quality